Fictions of the Press in Nineteenth-Century France - Birch, Edmund (Palgrave Studies in Modern European Literature, 2018)
This book explores how writers responded to the rise of the newspaper over the course of the nineteenth century. Taking as its subject the ceaseless intertwining of fiction and journalism at this time, it tracks the representation of newspapers and journalists in works by Honoré de Balzac, Edmond and Jules de Goncourt, and Guy de Maupassant. This was an era in which novels were published in newspapers and novelists worked as journalists. In France, fiction was to prove an utterly crucial presence at the newspaper's heart, with a gilded array of predominant literary figures active in journalism. Today, few in search of a novel would turn to the pages of a daily newspaper. But what are usually cast as discrete realms - fiction and journalism - came, in the nineteenth century, to occupy the same space, a point which complicates our sense of the cultural history of French literature.